Learning effect on labour productivity of repetitive concrete masonry blockwork: Fact or fable?. Issue 8 (14th November 2016) - Jarkas, Abdulaziz M.
Abstract : Purpose: The applicability of learning curve theory to the construction industry has been investigated by several studies; however, the outcomes are characterised by inconsistent, rather sporadic patterns. Therefore, the purpose of this paper is to explore the effect of learning on concrete masonry blockwork labour productivity in recurring building floor cycles. Design/methodology/approach: Repetitive blockwork labour inputs from 52 multi-storey residential buildings were collected and analysed using the straight-line learning curve model. The cumulative average labour input for each recurring floor and its corresponding cycle number were modelled using the least squares method. Findings: According to the learning curve theory principles, labour inputs are expected to decrease by a certain percentage as the floor cycle number within each building observed increases. Nonetheless, the patterns emerged from this study provide little evidence for that. Practical implications: Contrary to several previous findings which have asserted the significance of the learning concept to construction productivity, the results obtained for the activity investigated suggest that there is no potential context for the theory to be used as a useful tool to quantify productivity improvement, or to provide for a practical project management observation and control system. Originality/value: Notwithstanding the numerous research into the effect of learning on construction activities, this study is unprecedented in examining the applicability of the theory to concrete masonry blockwork labour productivity in building construction. It can thus assist in achieving reliable planning, determining the plausibility of correlating past performances or predicting future expenditures, and appraising the potentiality of the learning phenomenon as a useful tool to quantify productivity improvement over the repetitive cycle process of such a distinct construction activity.